(untitled) (Global Journal of Human-Social Science, 2023)
Language is a set of signs and symbols that serve as a tool for knowing Language is regarded as the most significant medium of communication and interaction among members of society in all walks of life People s cognitive activity is impossible without language Language is inextricably linked to thinking since human thoughts are constantly formed in a linguistic mold Journalistic writers use a variety of contemporary and historical materials to improve their writing including linguistic vernacular and standard citations and quotations from the native language and its vernaculars as well as foreign languages This study aims to examine the interference of English in Jordanian media through Mohammad Daoudia s articles as a model The study data were written by Daoudia and consisted of articles he published on Jordanian news website in January 2023 as a representative sample